The effect of different concentrations of cytokinin and auxin on in vitro culture of Physalis alkekengi (L.) using leaf and stem explants - Mona Kashanchi; Elaheh Pourfakhraei; Mitra Parsa; Amineh Zeinali (فیزیولوژی محیطی گیاهی, 2022)
Physalis alkekengi is a fruit-bearing plant in Iran. It is very popular due to the nutritional and medicinal properties. The main limitations of its cultivation are short reproductive cycle, fruits susceptibility to pests and limited information about crop management. The use of different micropropagation methods to produce physalis is proposed as practical solution. This study was conducted to evaluate the effect of culture medium and different concentrations of growth regulators on the seeds germination and organogenesis of P. alkekengi by using tissue culture technique as well as providing a suitable protocol for in vitro micropropagation of this plant. Seeds were cultured in 1/2 MS and distilled water with three different stabilizers including Plant Agar, Sand and Filter Paper. Direct regeneration (stem) and indirect regeneration (callusing from stem and leaf explants) were used for regeneration of the physalis. Explants were cultured in different hormone combinations of 6-Benzylaminopurine (BAP in 2 and 3 mg/L) and 2, 4-Dichlorophenoxyacetic acid (2, 4-D) (2 mg/L). The best seed germination medium was 1/2 MS contains plant agar as stabilizer (95%). The best explant for callusing was leaf and the best medium was ½ MS containing 2, 4-D (2 mg/ L). The best regeneration medium was BAP (3 mg / L) + GA3 (0.5 mg / L) on MS 1/2. The best hormone for direct organogenesis of stem was BAP at different concentrations. The best medium for micropropagation was ½ MS containing BAP (3 mg / L) + GA3 (0.5 mg / L) (more than 25 seedlings per explant). Rooting was performed using IBA (150 mg / L) followed by transferring seedlings to ½ MS after one week. Finally, seedlings were easily transferred to the soil and more than 95% of them survived in the greenhouse. These results suggest a protocol for commercial micropropagation of physalis plants.